C4 Index no. 0 : Contemporary Culture Centre Caldogno - Barbero, Luca Massimo; C4 - Centro Cultura Contemporaneo Caldogno, Caldogno (Caldogno : C4 - Centro Cultura Contemporaneo Caldogno, 2006)
Barbieri, Olivo ; Cecchini, Loris ; Charlton, Alan ; Duff, Arthur ; Eliasson, Olafur ; Garaicoa, Carlos ; Graham, Dan ; Jodice, Francesco ; Linke, Armin ; de Marchi, Riccardo ; Ontani, Luigi ; Orta, Jorge ; Orta, Lucy ; Pancrazzi, Luca ; Rehberger, Tobias ; Sassolino, Arcangelo ; Tremlett, David ; Umberg, Günter ; Verjux, Michel ; Zuffi, Italo
Publication on the occasion of the exhibition 'C4 Index no. 0: Contemporary Culture Centre Caldogno' at C4 - Centro Cultura Contemporaneo Caldogno in Caldogno. 2006-10-28
boek